Energy, exergy-emission performance investigation of heat exchanger with Turbulators inserts and ternary hybrid nanofluid - Rai R.; Kumar V.; Sahoo R.R. (My University, 2025)
Passive inserts, notably twisted turbulator inserts (TTI) and perforated twisted turbulator inserts (PTTI) loaded with water-based ternary hybrid nanofluid (THNF), are employed in plain tube heat exchangers to enhance thermal performance. The investigation focuses on how THNF replacement inserts will impact energy utilization, exergy consumption, and the environment in the decades to come. Nanoparticles of copper oxide (CuO), aluminum oxide (Al2O3), and titanium oxide (TiO2) are dissolved in water, which functions as the working fluid, and the resulting THNF is injected at three distinct concentrations (0.06, 0.09, and 0.12%). Certain aspects of the flow of a control fluid are investigated in terms of energy, exergy, and emissions. The experimental findings demonstrate that utilizing TTI and PTTI in conjunction with THNF substantially enhances the compact air heat exchanger's thermal and hydraulic efficiency. Heat transfer, friction factor, exergy change, and reversibility are greatly improved when turbulator inserts with PTTI and TTI are employed in plain tubes containing 0.12% (v/v) THNF. The CO2 discharge rises by 2.6–2.1 when PTTI or TTI turbulator inserts are inserted in the tube's core. Using PTTI with a concentration of 0.12% (v/v) THNF as the working fluid and a tube insert will provide PEC values in the range of 1.075–1.04. The thorough examination of heat transfer enhancement, friction factor, exergy efficiency, and environmental effect suggests that PTTI is a better passive device insert for heat transfer efficiency, particularly when combined with 0.12% (v/v) THNF. © Akadémiai Kiadó, Budapest, Hungary 2024.